Socialization of Financial Literacy For Millennial and Z Generations - Aslam, Annisa Paramaswary; Pratiwi, Andi Citra; Idris, Muhammad Istiyansyah Ulman; Abadi, Rahmat Riwayat; Syahrul, Khaidir (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2024)
Socialization were carried out on 2 November 2023 by Zoom platform. This event was organized by Seine Indonesia in collaboration with The FLASH Initiative. The activity was attended by 32 participants from 4 cities in Indonesia, namely Makassar, Jakarta, Surabaya, and Bandung. The first stage of this activity analysed the needs of PKM partners. After discussions and establishing a mission and vision, it was found that there was a need to provide financial literacy materials to the communities in several cities in Indonesia. Consequently, a session on financial literacy socialization was held, covering the importance of financial literacy, the benefits of financial planning, how to plan finances, and investment instruments in Indonesia. This socialization also aimed to protect the public from fraudulent investments. The results of this activity show that the level of financial literacy among Millennial and Z Generations is quite high. This is based on the investment activities they carry out and also financial behaviour such as recording expenses and income. From this financial literacy activity, it can be concluded that education about finance is very important to improve understanding and management of individual finances. Some suggestions that can be given include increasing awareness, giving financial literacy in elementary school, training for the societies, involvement of the private sector, and increasing government support in financial literacy.